CORPORATE FINANCIAL DISTRESS: : Contribuições da Contabilidade para a Sustentabilidade Corporativa no Brasil (ADMPG Journal, 2021)
The purpose of the article was to introduce a relevant approach capable of outlining a new path to guide the management of corporate financial distress in Brazil. It was noticed the existence of a time gap in the analysis of insolvency thermometer for monitoring the patrimony, identification of ways of solutions for preventive and corrective measures of the corporate financial distress. In relation to the existing gap, the impact of the article is the proposition of a trajectory that points to a new crucial point for the thermometer and alerts about the trend to the situation of the Corporate Financial Distress. The relevance of the article rests on the dissemination of a simple insolvency thermometer applicable to any business model for the purpose of predicting the business future.The research methodology has a qualitative, descriptive and documentary nature, although it contains quantitative methods to illustrate the financial distress presented at the selected company, Saraiva Livreiros S/A, a B3 listed company, participating in the new market in a situation of judicial reorganization. Although the research was supported by a publicly traded company due to the availability of important accounting reports and because it’s in a financial distress situation, it has an exemplary character to better elucidate the subject.The social contribution consists in the mitigation of corporate mortality by proposing a conservative way to manage financial distress.The results and contributions presented subsidies for understanding the insolvency thermometer in the light of the linear regression statistics that served as a parameter for validating the solvency situation. Additionally, it was the basis for the construction of a model named by the Author as a perpetuity thermometer based on conservatism related to the crucial moment of the insolvency thermometer to meet the uniqueness of each company regardless of size and location.Keywords: Corporate Financial Distress; corporate financial distress; corporate sustainability; crisis in Brazil